Peritoneal metastases from primary appendiceal and colorectal carcinomas demonstrate distinct molecular identities on comprehensive tumor analysis. Issue 5 (11th January 2023) - Fleming, Andrew M.; Deschner, Benjamin W.; Williard, Forrest W.; Drake, Justin A.; Vanderwalde, Ari; Xiu, Joanne; Somer, Bradley G.; Yakoub, Danny; Tsao, Miriam W.; Glazer, Evan S.; Dickson, Paxton V.; Shibata, David; et al.
Abstract: Background and Objectives: Published data comparing peritoneal metastases from appendiceal cancers (pAC) and colorectal cancers (pCRC) remain sparse. We compared pAC and pCRC using comprehensive tumor profiling (CTP). Methods: CTP was performed, including next‐generation sequencing and analysis of copy number variation (CNV), microsatellite instability (MSI) and tumor mutational burden (TMB). Results: One hundred thirty‐six pAC and 348 pCRC samples underwent CTP. The cohorts' age and gender were similar. pCRC demonstrated increased pathogenic variants (PATHs) in APC (48% vs. 3%, p  < 0.01), ARID1A (12% vs. 2%, p  < 0.01), BRAF (12% vs. 2%, p  < 0.01), FBXW7 (7% vs. 2%, p  < 0.01), KRAS (52% vs. 41%, p  < 0.05), PIK3CA (15% vs. 2%, p  < 0.01), and TP53 (53% vs. 23%, p  < 0.01), and decreased PATHs in GNAS (8% vs. 31%, p  < 0.01). There was no difference in CNV, fusion rate, or MSI. Median TMB was higher in pCRC (5.8 vs. 5.0 mutations per megabase, p  = 0.0007). Rates of TMB‐high tumors were similar (pAC 2.1% vs. pCRC 9.0%, p  = 0.1957). pCRC had significantly more TMB‐high tumors at lower thresholds. Conclusions: Despite a reduced overall TMB, pAC demonstrated mutations distinct from those seen in pCRC. These may serve as discrete biomarkers for future study.